2010
DOI: 10.1002/lary.21090
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic and socioeconomic disparities in the prevalence and treatment of otitis media in children in the United States

Abstract: Racial/ethnic and socioeconomic disparities exist for the prevalence and treatment of children with OM. Socioeconomic deprivation increases the risk of OM in children. Despite the frequency of tympanostomy tube insertion in children in the United States, few studies have addressed inequalities in access or utilization of surgical therapy. Given the changing healthcare climate and the social and economic impact of OM in children, further investigation of racial/ethnic and socioeconomic disparities targeting acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 39 publications
4
113
1
Order By: Relevance
“…For example, white children are more likely than black children to be referred to a subspecialist and to undergo placement of tympanostomy tubes. 6,[18][19][20] However, the role of tympanostomy tubes in the treatment of recurrent acute OM is debatable, 4 so it is unclear whether this translates into better care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, white children are more likely than black children to be referred to a subspecialist and to undergo placement of tympanostomy tubes. 6,[18][19][20] However, the role of tympanostomy tubes in the treatment of recurrent acute OM is debatable, 4 so it is unclear whether this translates into better care.…”
Section: Discussionmentioning
confidence: 99%
“…This study raises questions about whether physicians underdiagnose and undertreat OM among black children or overdiagnose and overtreat OM among nonblack children. Practice differences by race were apparent in previous studies from the 1990s and early 2000s, 2,6 but more recent studies have suggested that these practice differences may have attenuated. 2,[6][7][8][9] Our objectives were to determine whether national racial disparities currently exist in the diagnosis of OM or in the antibiotic choice for OM in children.…”
mentioning
confidence: 93%
“…Other relevant factors are season (greater AOM prevalence in autumn and winter) [Lubianca Neto et al, 2006], urbanisation (increased risk) [Paradise et al, 1997] and use of a pacifier (increased risk) [Uhari et al, 1996;Lubianca Neto et al, 2006]. The contribution of gastro-oesophageal reflux disease [Lubianca Neto et al, 2006] or socioeconomic deprivation [Smith and Boss, 2010] to risk is uncertain.…”
Section: The Exposomementioning
confidence: 99%
“…These differences could be due to ethnic variations in socio-economic factors (Vernacchio et al 2004) or in illness-seeking behavior (Park et al 2002), as well as genetics, but because many studies have been retrospective they have been unable to control for such confounders. Furthermore studies have been contradictory, and the conclusions of systematic (Smith & Boss 2010) relatively small total and demic population sizes, and each of these populations lived in relative geographic and social isolation. Hence, for the large part they were exposed only to local or regional microorganisms.…”
Section: Ethnic Variations In Otitis Media Incidencementioning
confidence: 99%